2022
DOI: 10.3390/microorganisms10061118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Inhalation Therapy on Ventilator-Associated Pneumonia in Ventilated COVID-19 Patients: A Randomized Controlled Trial

Abstract: The effect of routine inhalation therapy on ventilator-associated pneumonia (VAP) in mechanically ventilated patients with the coronavirus disease (COVID-19) has not been well-defined. This randomized controlled trial included 175 eligible adult patients with COVID-19 who were treated with mechanical ventilation at the University Hospital of Split between October 2020 and June 2021. Patients were randomized and allocated to a control group (no routine inhalation) or one of the treatment arms (inhalation of N-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The 14 remaining articles underwent a full-text review for eligibility assessment. Finally, this study identified a total of five RCTs [ [17] , [18] , [19] , [20] , [21] ] that met the inclusion criteria. The algorithm for study selection is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 14 remaining articles underwent a full-text review for eligibility assessment. Finally, this study identified a total of five RCTs [ [17] , [18] , [19] , [20] , [21] ] that met the inclusion criteria. The algorithm for study selection is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the five included studies [ [17] , [18] , [19] , [20] , [21] ]. One study [ 21 ] was a phase 2 RCT, and the other four were phase 3 studies [ [17] , [18] , [19] , [20] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 10. Random effects meta-analysis for all RCTs about alkalinization in COVID-19 [119][120][121][122][123][124][125][126]. This plot shows pooled effects, see the specific outcome analyses for individual outcomes, and the heterogeneity section [21] for discussion.…”
Section: Nose/oropharyngeal Treatmentsmentioning
confidence: 99%